2021
DOI: 10.1002/app.50996
|View full text |Cite
|
Sign up to set email alerts
|

Elastohydrodynamic lubrication analysis of polymer‐on‐polymer artificial hip joint of CF/PEEK composite

Abstract: At present, the main frictional components of artificial hip joint (AHJ) are mainly the combinations of hard materials (metal, ceramic) and soft materials (polymer), such as, metal‐on‐metal (MoM), ceramic‐on‐ceramic (CoC), metal‐on‐polymer (MoP), and ceramic‐on‐polymer (CoP). As a new type of AHJ, the polymer‐on‐polymer (PoP) combination has gradually begun to be explored and studied. In this paper, PoP AHJ of CF/PEEK composite are studied, and elastohydrodynamic lubrication analysis based on the solution of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The specific solution strategy can refer to the authors' previous work. 33 The accuracy of the EHL analysis is also crucial for the shape optimization of the AHJ, and it is affected by the mesh density of the model. According to the numerical tests, when the mesh density is higher than 100 Â 100, the influence on the thickness distribution of the lubricating film is relatively small, and the change of the lubricating film thickness tends to be stable.…”
Section: Governing Equations and Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific solution strategy can refer to the authors' previous work. 33 The accuracy of the EHL analysis is also crucial for the shape optimization of the AHJ, and it is affected by the mesh density of the model. According to the numerical tests, when the mesh density is higher than 100 Â 100, the influence on the thickness distribution of the lubricating film is relatively small, and the change of the lubricating film thickness tends to be stable.…”
Section: Governing Equations and Solutionmentioning
confidence: 99%
“…The authors recently proposed a CF/PEEK polymeron-polymer AHJ model and analyzed its EHL performance, and the results showed that it had better lubrication performance than the traditional metal-onpolymer or metal-on-metal AHJ. 33 On this basis, combined with EHL analysis and the simulated annealing (SA) method, a shape optimization strategy for the femoral head of the CF/PEEK AHJ is proposed in this work, so as to obtain better lubrication performance and provide theoretical support for the novel design of the AHJ.…”
mentioning
confidence: 99%